2016
DOI: 10.11118/actaun201664020635
|View full text |Cite
|
Sign up to set email alerts
|

Economic Multipliers and Sectoral Linkages: Ghana and the New Oil Sector

Abstract: The study seeks to assess the structure of the economy of Ghana in terms of changes in the economic structure before and after the production of oil in commercial quantities. This is viewed with regards to economic multipliers, sectoral interdependence and trade concentration. The results show that changes occurred with regards to multipliers and sectoral interdependence. The output multipliers of most sectors have declined. The results also show that the agricultural sector experienced an initial decline in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Similarly, the agricultural sector is investigated for the period of 1952-2010 for Pakistan and it is concluded that modern technologies has the potential to increase the contribution of the agriculture sector on the economic growth (Zaheer, 2013). In another study, the economic data of Ghana is analysed for the 2009-2013 period and it is shown that the share of the agricultural sector in the gross domestic product has increased from 20% to 30% from 2009 to 2013, increasing the importance of the agricultural revenue for the gross domestic product (Nchor and Konderla, 2016). The employment shares of the agricultural sector in the gross domestic products of several countries are studied in another paper where it is exposed that the share of the employment in the agriculture sector are 42% in South Asia, 31% in sub-Saharan Africa, 40% in China, 27% in North Africa and 4% in high income countries in the period of 2000-2015 (FAO of UN, 2018).…”
Section: Literature Surveymentioning
confidence: 99%
“…Similarly, the agricultural sector is investigated for the period of 1952-2010 for Pakistan and it is concluded that modern technologies has the potential to increase the contribution of the agriculture sector on the economic growth (Zaheer, 2013). In another study, the economic data of Ghana is analysed for the 2009-2013 period and it is shown that the share of the agricultural sector in the gross domestic product has increased from 20% to 30% from 2009 to 2013, increasing the importance of the agricultural revenue for the gross domestic product (Nchor and Konderla, 2016). The employment shares of the agricultural sector in the gross domestic products of several countries are studied in another paper where it is exposed that the share of the employment in the agriculture sector are 42% in South Asia, 31% in sub-Saharan Africa, 40% in China, 27% in North Africa and 4% in high income countries in the period of 2000-2015 (FAO of UN, 2018).…”
Section: Literature Surveymentioning
confidence: 99%
“…Input–output tables have been used to calculate multipliers for the Ghanaian economy (Nchor 2014 ; Bentum-Ennin 2018 ) and to analyse the sectoral linkages for the specific case of the oil sector (Nchor and Konderla 2016 ). However, due to the characteristics of the Ghanaian economy, the SAM multiplier models are more appropriated tools, as they allow closing the circular flow of income and expenditure, taking into account household-related socio-economic data from household budget and labour force surveys.…”
Section: Introductionmentioning
confidence: 99%